Pharmacological Modulation of Mitochondrial Ca2+ Content Regulates Sarcoplasmic Reticulum Ca2+ Release via Oxidation of the Ryanodine Receptor by Mitochondria-Derived Reactive Oxygen Species - Hamilton, Shanna; Terentyeva, Radmila; Kim, Tae Yun; Bronk, Peter; Clements, Richard T.; O-Uchi, Jin; Csordás, György; Choi, Bum-Rak; Terentyev, Dmitry (Frontiers in Physiology, 2018)
In a physiological setting, mitochondria increase oxidative phosphorylation during periods of stress to meet increased metabolic demand. This in part is mediated via enhanced mitochondrial Ca2+ uptake, an important regulator of cellular ATP homeostasis. In a pathophysiological setting pharmacological modulation of mitochondrial Ca2+ uptake or retention has been suggested as a therapeutic strategy to improve metabolic homeostasis or attenuate Ca2+-dependent arrhythmias in cardiac disease states. To explore the consequences of mitochondrial Ca2+ accumulation, we tested the effects of kaempferol, an activator of mitochondrial Ca2+ uniporter (MCU), CGP-37157, an inhibitor of mitochondrial Na+/Ca2+ exchanger, and MCU inhibitor Ru360 in rat ventricular myocytes (VMs) from control rats and rats with hypertrophy induced by thoracic aortic banding (TAB). In periodically paced VMs under β-adrenergic stimulation, treatment with kaempferol (10 μmol/L) or CGP-37157 (1 μmol/L) enhanced mitochondrial Ca2+ accumulation monitored by mitochondrial-targeted Ca2+ biosensor mtRCamp1h. Experiments with mitochondrial membrane potential-sensitive dye TMRM revealed this was accompanied by depolarization of the mitochondrial matrix. Using redox-sensitive ERroGFP_iE biosensor, we found treatment with kaempferol or CGP-37157 increased the levels of reactive oxygen species (ROS) in the sarcoplasmic reticulum (SR). Confocal Ca2+ imaging showed that accelerated Ca2+ accumulation reduced Ca2+ transient amplitude and promoted generation of spontaneous Ca2+ waves in VMs paced under ISO, suggestive of abnormally high activity of the SR Ca2+ release channel ryanodine receptor (RyR). Western blot analyses showed increased RyR oxidation after treatment with kaempferol or CGP-37157 vs controls. Furthermore, in freshly isolated TAB VMs, confocal Ca2+ imaging demonstrated that enhancement of mito-Ca2+ accumulation further perturbed global Ca2+ handling, increasing the number of cells exhibiting spontaneous Ca2+ waves, shortening RyR refractoriness and decreasing SR Ca2+ content. In ex vivo optically mapped TAB hearts, kaempferol exacerbated proarrhythmic phenotype. On the contrary, incubation of cells with MCU inhibitor Ru360 (2 μmol/L, 30 min) improved intracellular Ca2+ homeostasis and reduced triggered activity in ex vivo TAB hearts. These findings suggest facilitation of mitochondrial Ca2+ uptake in cardiac disease can exacerbate proarrhythmic disturbances in Ca2+ homeostasis via ROS and enhanced activity of oxidized RyRs, while strategies to reduce mitochondrial Ca2+ accumulation can be protective.